Formal Features Of Image Construction In Ghost Films (Al-Academy, 2024)
Ghosts - as a cultural phenomenon inherited across generations - represent a fundamental element created by the human imagination and addressed in literary and cinematic narratives, as ghosts occupy a large space in the heritage of nations. Horror films have emerged, especially ghost films, which are prominent film genres that derive their themes from the myths and legacy of ancient civilizations, in which they address events shrouded in mystery in all their details, from place and time, especially the presence of supernatural characters belonging to strange forms and hostile actions, which arouse tension and fear in the recipients. Due to the popularity and popularity of this type of film, modern cinema has worked to increase the element of suspense by producing ghostly images and sounds that have been processed using innovative artistic methods that contain in their narrative structure extremely complex plots that provoke fear, panic and terror, relying on the technological development that has included the film production sector with all its technical joints at the levels of image and sound, so that these ghostly creatures have artistic metaphors for realistic topics that touch on human life, perceptions and changing culture. From this standpoint, the researcher found it necessary to research the formal characteristics of ghost films. She formulated her research problem with the following question: (What are the formal characteristics required to build the image in ghost films?). The research also included the following axes: a summary of the research, including the introduction and the research problem, then its importance and the need for it, as the importance was represented in shedding light on the formal characteristics of ghost films, while the aim of the research lies in identifying the formal characteristics of this sub-film genre, then defining the terms. The theoretical framework of the research included two topics: the first dealt with the phenomenon of ghosts and their types, while the second dealt with the structure of the image in ghost films and the most important techniques used to represent them. These topics resulted in several indicators that the researcher used to analyze the selected film sample. The research concluded with a set of results, namely: Ghosts have the ability to appear in a manner that suits current events and in a way that makes other characters sympathize with them. Also, the possession of ghosts of supernatural powers - most notably appearance and disappearance - is what enabled them to communicate with the living to achieve their goal of salvation or revenge on those who caused them harm. Ghosts often emerge from deserted, isolated or remote places, taking them as a place to build their lives, as they are a suitable environment (and compatible with the stereotypical image of ghosts among individuals) to arouse awe and terror. Ghost films are characterized by dark atmospheres, as most of their scenes depend on dim lighting. The most important conclusions of the study: The continued production and follow-up of ghost films reflects the fact that this genre has its own formal and structural features, in addition to the continued interest of societies in the supernatural. Ghost films are not limited to stories based on myths or fantasy, but can also be based on fictional events integrated with real stories. To achieve the continuity and attractiveness of this sub-genre of film. Ghost films are based on special places, to be the main source for creating ghosts that arouse the instinct of fear. The research concluded with a list of sources and a summary in English